Effect of ultrasonic degradation on the physicochemical property and bioactivity of polysaccharide produced by Chaetomium globosum CGMCC 6882 - Li, Shiwei; Wang, Yingna; Dun, Weipeng; Han, Wanqing; Xu, Chunping; Sun, Qi; Wang, Zichao (Frontiers in Nutrition, 2022)
Similar to enzymatic process, there might also be active fragment in polysaccharides, how to obtain which is important for investigating the bioactivity and pharmacological mechanism of polysaccharides. Presently, a Gynostemma pentaphyllum endophytic fungus Chaetomium globosum CGMCC 6882 polysaccharide (GCP) was degraded by ultrasonic treatment, two polysaccharide fragments of GCP-F1 and GCP-F2 were obtained. Physicochemical results showed that GCP-F1 and GCP-F2 had the same monosaccharide composition of arabinose, galactose, glucose, xylose and mannose and glucuronic acid compared to GCP with slightly different molar ratios. However, weight-average molecular weights of GCP-F1 and GCP-F2 decreased from 8.093 × 104 Da (GCP) to 3.158 × 104 Da and 1.027 × 104 Da, respectively. In vitro scavenging assays illustrated that GCP-F1 and GCP-F2 had higher antioxidant activity against ABTS radical, DPPH radical, superoxide anions and hydroxyl radical than GCP, the order was GCP < GCP-F1 < GCP-F2. Meanwhile, antibacterial tests showed that ultrasonic degradation increased the antibacterial activity of GCP-F1 compared to GCP, but GCP-F2 almost lost its antibacterial activity with further ultrasound treatment. Changes of the antioxidant and antibacterial activities of GCP-F1 and GCP-F2 might related to the variation of their molecular weights.